2016
DOI: 10.1002/cctc.201600037
|View full text |Cite
|
Sign up to set email alerts
|

Visible‐Light‐Mediated Aromatic Substitution Reactions of Cyanoarenes with 4‐Alkyl‐1,4‐dihydropyridines through Double Carbon–Carbon Bond Cleavage

Abstract: Novel aromatic substitution reactions of cyanoarenes with 4‐alkyl‐1,4‐dihydropyridines as alkylating reagents in the presence of a catalytic amount of a photoredox catalyst proceed smoothly to give the corresponding alkyl‐substituted arenes in good to high yields. The present reaction system realizes a novel C−C bond‐forming reaction between two fragments generated from the C−C bond‐cleavage reactions of two independent substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
94
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(95 citation statements)
references
References 60 publications
0
94
0
1
Order By: Relevance
“…We believe that the homolysis of the DHP unit occurs via formation of a radical cation, followed by a deprotonation step, forming an aminyl radical that will then undergo homolysis. 15,16 Notably, we observed that 1c- N -Me (the N -methylated analogue of 1c ) failed to deliver the cross-coupling product under reaction conditions, thus supporting the deprotonation prior to the C–C cleavage event hypothesis. 15a …”
mentioning
confidence: 60%
“…We believe that the homolysis of the DHP unit occurs via formation of a radical cation, followed by a deprotonation step, forming an aminyl radical that will then undergo homolysis. 15,16 Notably, we observed that 1c- N -Me (the N -methylated analogue of 1c ) failed to deliver the cross-coupling product under reaction conditions, thus supporting the deprotonation prior to the C–C cleavage event hypothesis. 15a …”
mentioning
confidence: 60%
“…[51,52] [52] die in Umwandlungen reagieren kçnnen, wie beispielsweise aromatischer Substitution. [53] Zwei Arbeitsgruppen [54,55] berichteten über die Kreuzkupplung von Arylhalogeniden und Alkyl-DHPs.E ine Gruppe verwendete eine Base zur Deprotonierung des DHP und Bildung einer leichter oxidierbaren anionischen Spezies (Schema 4A). Die zweite Arbeitsgruppe setzte anstelle der Base den oxidativeren 4CzIPN-Photokatalysator 4 ein (Abbildung 1).…”
Section: Kupplungen Mit Dihydropyridinen Als Radikalvorstufenunclassified
“…[11,12] These alkylation reagents have been used in photochemical reactions [11a, 12] and thermal reactions with Lewis acid catalysts [11b] or radical initiators. [12,14] In this reaction system, ak ey step is the generation of alkyl radicals as reactive intermediates by single-electron oxidation of 4-alkyl-1,4-dihydropyridines. [12,14] In this reaction system, ak ey step is the generation of alkyl radicals as reactive intermediates by single-electron oxidation of 4-alkyl-1,4-dihydropyridines.…”
mentioning
confidence: 99%